Clinical Observation of Sling Exercise Combining Plucking Bladder Meridian on Treating Low Back Muscle Fasciitis - Fei LI; LI Li; Qiangqiang XU; Jiapeng ZHANG (康复学报)
Objective:To investigate the clinical effect of sling exercise combining plucking bladder meridian on treating low back muscle fasciitis.Methods:A total of 120 patients with low back muscle fasciitis were randomly assigned to sling exercise therapy group, plucking bladder meridian group, and sling exercise therapy and plucking bladder meridian manipulation combined treatment group, with forty patients in each group, and treated once per day, 5 treatments per week, 3 weeks for a course, whole treatment contain 2 courses. The visual analogue scale (VAS) score and oswestry dysfunction index (ODI) score of the three groups were evalued and analyzed respectively before and after treatment and follow-up.Results:After treatment, VAS score and ODI score of three groups were all improved, and the difference was statistically significant (P<0.05), The combined group was superior to two other groups with statistically significant difference (P<0.05) respectively. VAS score and ODI score of the combined group got more improvment during the follow-up than those of other groups (P<0.05).Conclusion:The sling exercise therapy combined plucking bladder meridian had a significant effect in the treatment of low back muscle fasciitis, and could improve the function of low back muscle.